127 Consider a Meromorphic Function F : C → C with Laurent Series F(Z) = P∞ N N=−∞ Cnz at the Origin

127 Consider a Meromorphic Function F : C → C with Laurent Series F(Z) = P∞ N N=−∞ Cnz at the Origin

COMPLEX ANALYSIS HW 4 CLAY SHONKWILER 127 Consider a meromorphic function f : C → C with Laurent series f(z) = P∞ n n=−∞ cnz at the origin. Find a necessary and sufficient condition on the complex coefficients (cn) so that f(R) ⊆ R. Claim: If f : C → C is a meromorphic function with Laurent series P∞ n f(z) = n=−∞ cnz at the origin, then f(R) ⊆ R if and only if cn ∈ R for all n ∈ Z. Proof. If cn ∈ R for all n, then certainly f(R) ⊆ R, so we need only prove that the coefficients being in R is a necessary condition for f(R) ⊆ R. To that end, suppose f(R) ⊆ R. Since f is meromorphic, there can only be finitely many negative terms in the Laurent expansion, so there exists N ∈ N P∞ n such that f(z) = n=−N cnz and c−N 6= 0. Thus, we can re-write f as ∞ ∞ X 1 X f(z) = c zn = c zn. n zN n−N n=−N n=0 P∞ n N Let g(z) = n=0 cn−N z . Then z f(z) = g(z). Now, if r ∈ R, then N r ∈ R and f(r) ∈ R; since the product of two reals is real, this implies that g(r) ∈ R. Since our choice of r was arbitrary, we see that g(R) ⊆ R. To deal with this situation, let us first prove a small lemma: 0 Lemma 0.1. If h ∈ H(C) such that h(R) ⊆ R, then h (R) ⊆ R. Proof. By definition of the derivative, h(z + ζ) − h(z) h0(z) = lim ζ→0 ζ for any z ∈ C. Now, if z ∈ R and ζ = k ∈ R, then h(z+k) ∈ R and h(z) ∈ R, so h(z + k) − h(z) ∈ R. Therefore, since the derivative is well-defined, 0 h(z + k) − h(z) h (z) = lim ∈ R. k→0 k 0 Since our choice of z ∈ R was arbitrary, we conclude that h (R) ⊆ R. First, note that ∞ X n g(0) = cn−N 0 = c−N ∈ R. n=0 1 2 CLAY SHONKWILER Now, since g is holomorphic and g(R) ⊆ R, we can apply the above lemma 0 to conclude that g (R) ⊆ R. Now, ∞ 0 X n−1 g (z) = ncn−N z , n=1 so ∞ 0 X n−1 g (0) = ncn−N 0 = c1−N ∈ R. n=1 0 00 g also satisfies the hypotheses of the lemma, so g (R) ∈ R, and so ∞ 00 X n−2 g (0) = n(n − 1)cn−N 0 = 2c2−N ∈ R n=2 so c2−N ∈ R. Iterating this process, we see that at the jth stage, ∞ (j) X n−j g (0) = n(n − 1) ··· (n − (j + 1))cn−N 0 = j(j − 1) ··· 2 · 1cj−N ∈ R n=j and so cj−N ∈ R. Therefore, we conclude that cn ∈ R for all n. 2 Let ζ be a point in the unit disk and f ∈ H(D\{ζ}). Show that for all sufficiently small > 0 Z Z f(z)dz = f(z)dz. |z|=1 |z−ζ|= Be careful, use only results that have been established in this course! If E = {ζ1, . , ζN } are points in D, and f ∈ H(D\E), then show that, for sufficiently small > 0, N Z X Z f(z)dz = f(z)dz. |z|=1 j=1 |z−ζj |= Proof. Since f is holomorphic on the unit disk except at ζ, if ρ = min|z|=1{|ζ− z|}, then f has a Laurent expansion in Dρ(ζ)\{ζ} given by ∞ X n cn(z − ζ) . n=−∞ Furthermore, this converges uniformly on any compact subset of Dρ(ζ)\{ζ}. In fact, as |z − ζ| gets larger, the sum −1 X n (1) g(z) = cn(z − ζ) n=−∞ converges more and more rapidly, so in fact g ∈ H(C\{ζ}). Now, let h(z) = f(z) − g(z). COMPLEX ANALYSIS HW 4 3 Then, since f ∈ (D\{ζ}) and g ∈ H(C\{ζ}), h is holomorphic on D\{ζ}. Now, ζ is a removable singularity of h, since in Dρ(ζ)\{ζ} ∞ X n f(z) = cn(z − ζ) + g(z) n=0 and so ∞ X n h(z) = f(z) − g(z) = cn(z − ζ) n=0 in this neighborhood, meaning we can analytically continue h at ζ using this power series. In doing so, we now have h ∈ H(D); hence, by Cauchy- Goursat, Z h(z)dz = 0 γ for any closed curve γ ∈ D. Since f(z) = g(z) + h(z) away from ζ, Z Z Z Z f(z)dz = g(z)dz + h(z)dz = g(z) γ γ γ γ for any γ that doesn’t pass through ζ. Since the sum in (1) converges uniformly outside any small disc centered at ζ, it converges uniformly on γ and so Z −1 Z ∞ Z X X c−n g(z)dz = c (z − ζ)ndz = dz. n (z − ζ)n γ n=−∞ γ n=1 γ Now, if n > 1, then 1 d −1 = (z − ζ)n dz (n − 1)(z − ζ)n−1 so, by the result proved in problem 1 of homework 2, Z c−n −c−n −c−n n dz = n−1 − n−1 = 0 γ (z − ζ) (n − 1)(γ(1) − ζ) (n − 1)(γ(0) − ζ) since γ is a closed curve and so γ(1) = γ(0). Therefore, Z Z Z Z c−1 1 f(z)dz = g(z)dz = dz = c−1 dz. γ γ γ z − ζ γ z − ζ Since this is true for any closed γ ∈ D\{ζ}, the above result holds for γ denoting the circle |z| = 1 − δ for any δ > 0, and so we see that Z Z 1 (2) f(z)dz = c−1 dz. |z|=1 |z|=1 z − ζ Now, Z 1 dz = 2πi |z|=1 z − ζ by Cauchy’s Integral Formula, since the function 1 is holomorphic in D. 4 CLAY SHONKWILER 1 R Now, recall that c−1 is defined to be 2πi |z−ζ|= f(z)dz for 0 < < ρ. Hence, plugging this data into (2), we see that Z 1 Z Z f(z)dz = f(z)dz2πi = f(z)dz. |z|=1 2πi |z−ζ|= |z−ζ|= To prove the case where f ∈ H(D\E) where E = {ζ1, . , ζN }, let ρ0 = min{|ζ1 − z|,..., |ζN − z|}, |z|=1 let ρi = min{|ζi − ζj|} j6=i and let ρ = min {ρi}. 0≤i≤N Then for each i = 1,...,N, f is holomorphic on the punctured disc of radius ρ centered at ζi and so, for each i, ∞ X ni f(z) = cni z ni=−∞ on Dρ(ζi)\{ζi}. Let −1 X ni (3) gi(z) = cni z n=−∞ and let N X g(z) = gi(z) i=1 Then, by the same argument for the g defined above, g is holomorphic on C\E and so h(z) = f(z) − g(z) is holomorphic on D\E. Now, in Dρ(ζi), ∞ X ni h(z) = f(z) − g(z) = cni (z − ζi) , ni=0 so each ζi is a removable singularity of h, which we can, thus, extend to a holomorphic function on all of D. Thus, by Cauchy-Goursat, Z h(z)dz = 0 γ for any closed curve γ in D. Since f(z) = g(z) + h(z) away from ζi, Z Z Z Z f(z)dz = g(z)dz + h(z)dz = g(z) γ γ γ γ COMPLEX ANALYSIS HW 4 5 P for any γ that doesn’t pass through any of the ζi. Since g = gi is a finite sum, we can swap sum and integral to see that N Z X Z (4) f(z)dz = gi(z). γ i=1 γ Furthermore, since γ does not pass through any of the ζi, there is some δ > 0 such that Dδ(ζi) does not intersect γ for all i; since the sum in (3) converges uniformly outside Dδ(ζi), at ζ, it converges uniformly on γ and so Z −1 Z ∞ Z c X ni X −ni gi(z)dz = cni (z − ζ) dz = n dz. γ γ γ (z − ζ) i ni=−∞ ni=1 Now, if ni > 1, then 1 d −1 n = n −1 (z − ζ) i dz (ni − 1)(z − ζ) i so, by the result proved in problem 1 of homework 2, Z c−ni −c−ni −c−ni n dz = n −1 − n −1 = 0 γ (z − ζ) i (ni − 1)(γ(1) − ζ) i (ni − 1)(γ(0) − ζ) i since γ is a closed curve and so γ(1) = γ(0). Therefore, Z Z Z c−1i 1 gi(z)dz = dz = c−1i dz. γ γ z − ζ γ z − ζ Since this is true for any closed γ ∈ D\E, the above result holds for γ denoting the circle |z| = 1 − δ for any ρ > δ > 0, and so we see that Z Z 1 (5) gi(z)dz = c−1i dz. |z|=1 |z|=1 z − ζ Now, Z 1 dz = 2πi |z|=1 z − ζi by Cauchy’s Integral Formula, since the function 1 is holomorphic in D. 1 R Now, recall that c−1 is defined to be f(z)dz for 0 < < ρ. i 2πi |z−ζi|= Hence, plugging this data into (5), we see that Z 1 Z Z gi(z)dz = f(z)dz2πi = f(z)dz. |z|=1 2πi |z−ζi|= |z−ζi|= Therefore, by (4), N N Z X Z X Z f(z)dz = gi(z)dz = f(z)dz |z|=1 i=1 |z|=1 i=1 |z−ζi|= for any < ρ.

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    12 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us